Implementasi Teori Hadis Maudū’ dalam Menilai Kredibilitas Portal Berita: Analisis pada Portal Media Tirto.id - Wahid, Abdul Hakim; Mudhii’ah, Sakinah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Implementation of Maudū' Hadith Theory in Assessing the Credibility of News Portals: Analysis on the Tirto.id Media PortalMedia portals have a number of drawbacks in presenting news. One of them is incomplete information due to the reporting and writing that rushes to present the news. In addition, a lot of hoax information circulates in the community through portal media because of the writing of titles or click baits so that people tend to swallow the news raw without reading the entire content of the news. Therefore, the news circulating in the port media needs to be further investigated regarding the truth. This research used a library study (Library Research). With the first research method, collected a sample of news in the media portal Tirto. Second, analyze the sample of news in the media of the Tirto portal using the theory of maudū' hadith. This research proves that tirto.id in their reporting still prioritize the accuracy of news. Therefore, news portals tirto.id can be said to be media that have high trust and credibility. Credibility here is rested on the depth of the news presented, true and accurate information and factual according to the facts